The Agricultural Associations in Kharkiv Province: Creation and Trends of the Activity (1880 -1914) - Lysenko, Maya (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 1970)
The article deals with a research of an activity of agricultural societies in Kharkiv province. The author has studied their origin, development, types and quantity. There were province, uyezd and rural agricultural associations. They composed all spheres of agriculture of the region. Kharkiv Agricultural Society was the most effective one. Its work was extended for six neighbouring provinces of the Russian Empire. The representative of different social and professional groups, such as entrepreneurs, officials of zemstvo, scientists and landowners collaborated in the agricultural associations. These public associations had great influence on agricultural sphere of economy and the modernization of publicity in this region.